2020
DOI: 10.3329/bioethics.v9i3.48913
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence in Bangladesh: A Scoping Review

Abstract: Introduction: Intimate Partner Violence (IPV) has unfavorable consequences for women as well as for newborn babies, which is very serious and preventable public health problem. It is believed to have an excessive occurrence in lives of women in South Asia. The objective of this study is to describe the prevalence, risk factors and consequences of IPV in Bangladesh. Methods: A scoping review was carried out based on the past 12 years of posted and gray literature about IPV in Bangladesh using Arksey and O’Malle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…This was also found to be the case in the United Kingdom, where a similar group of women exhibited moderate to severe anxiety and depressive symptoms [ 13 ]. A systematic review reported the major risk factors for depression and anxiety among women with spontaneous abortions [ 14 ]. A review stated anxiety was common among women with a history of poor mental health, lower spousal support, no children, a history of miscarriage, and unplanned and assisted pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…This was also found to be the case in the United Kingdom, where a similar group of women exhibited moderate to severe anxiety and depressive symptoms [ 13 ]. A systematic review reported the major risk factors for depression and anxiety among women with spontaneous abortions [ 14 ]. A review stated anxiety was common among women with a history of poor mental health, lower spousal support, no children, a history of miscarriage, and unplanned and assisted pregnancy.…”
Section: Introductionmentioning
confidence: 99%